Implementasi Pendidikan Politik bagi Pemilih Pemula Terhadap Pemilihan Umum 2024: Implementation of Political Education for First-Time Voters Ahead of the 2024 General Election - Abdulloh Hasyim (SIYASI: Jurnal Trias Politica, 2023)
Implementation of law number 2 of 2008 concerning political parties regarding political education for first-time voters in the 2024. General election the importance of political education for first-time voters in the 2024 general election is to become intelligent voters and understand the political dynamics that are occurring. This research aims to find out how political education is implemented for novice voters. How is the participation of novice voters in carrying out the 2024. General election. This research uses normative legal methods. Data collection techniques use literature study. Data was tested by source triangulation. Data analysis techniques go through the stages of data collection, data reduction, data presentation, and drawing conclusions.